Respuesta :

answer: 10.4

explanation: a^2 + b^2 = c^2
plug in 3 for a and 10 for b
3^2 + 10^2 =c^2
simplify to get
109 =c^2
take the square root of both sides
c = sqrt109 or 10.44030651

Answer:

c (the hypotenuse) = 10.4 units

Step-by-step explanation:

Start off by rearranging the original pythangorean theorem (a^2+b^2=c^2) by taking the square root of both sides so it is in the form of a distance formula solving for c(the hypotenuse).

c^2 will become |c| as length cannot be negative so (labeling an absolute value is negligible)

a^2+b^2 = c^2

c^2 = a^2+b^2

√(c^2) = √(a^2+b^2)

c = √(a^2+b^2)

Then substitute the given lengths, in this scenario, sides a and b.

After you substitute, just simplify.

c = √(3^2+10^2) = √(9+100) = √109 ≈ 10.4 units (nearest tenth)